High-pressure hydrogen effects on thermoplastics: A comprehensive review of permeation, decompression failure, and mechanical properties - Jiacheng Zhao; Guozhen Ding; Peng Feng; Chao Wu (Advanced Industrial and Engineering Polymer Research, 2025)
Hydrogen energy is widely regarded as a clean and sustainable alternative to fossil fuel. Among various hydrogen storage options, high-pressure gas cylinders, especially Type IV composite cylinders, are increasingly used due to their light weight and high storage efficiency. Since the thermoplastic liner plays a significant role as a permeation barrier of the total cylinder, the current research findings and gaps related to its properties under high-pressure hydrogen environments are reviewed. Firstly, the potential thermoplastics and processing techniques of the liner are presented. Then, the review focuses on three key properties of thermoplastic liners including permeability, decompression failure and mechanical properties under high-pressure hydrogen environments. The mechanism and key influencing factors of these properties are systematically discussed, followed by the proposal of targeted and valuable improvement strategies. Moreover, testing and standards, quantification and physical models of these three properties are also outlined to provide guidance and reference for future research and applications. In the end, the research gaps and future perspectives related to the thermoplastic liner are identified. This review provides a valuable reference for the performance optimization and engineering application of the thermoplastic liners of Type IV cylinders.